Managing the fiscal metropolis : the financial policies, practices, and health of suburban municipalities - Hendrick, Rebecca Martin (American governance and public policy., 2011)
Managing the Fiscal Metropolis: The Financial Policies, Practices, and Health of Suburban Municipalities is an important book. This first comprehensive analysis of the financial condition, management, and policy making of local governments in a metropolitan region offers local governments currently dealing with the Great Recession a better understanding of what affects them financially and how to operate with less revenue. Hendrick's groundbreaking study covers 264 Chicago suburban municipalities from the late 1990s to the present. In it she identifies and describes the primary factors and eve.